CURRICULUM AND THE PATTERN OF CONCENTRATIONSMK AND ITS RELEVANCE TO PROGRAM STUDI PENDIDIKAN TEKNIK MESIN UNIVERSITY OF PALANGKARAYA - Sri Murwantini (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2015)
The Program Studi has the obligation to draw up a curriculum, implement, and evaluate the implementation of the curriculum refers to KKNI field of higher education in accordance with the policies, regulations, and guidance on the preparation of the course curriculum. Become link and match, curriculum development Program Studi Pendidikan Teknik Mesin University of Palangkaraya need to pay attention in particular vocational curriculum of Automotive Engineering Program. The structure of vocational curriculum comprises general subjects ( Group A and B ) and the subjects of specialization (Group C1, C2, and C3). Concentration is done in two (2) phases, namely concentrationexpertiseprogram at the time of a new student skills and interests package upon completing the class X. Curriculum Program Studi Pendidikan Teknik Mesin University of Palangkaraya in general is relevant for vocational curriculum Automotive Engineering Program.